MiR-21-3p Promotes Hepatocellular Carcinoma Progression via SMAD7/YAP1 Regulation - Hong, Yinghui; Ye, Mingliang; Wang, Fan; Fang, Jun; Wang, Chun; Luo, Jie; Liu, Jialiang; Liu, Jing; Liu, Lan; Zhao, Qiu; Chang, Ying (Frontiers in Oncology, 2021)
Background Hepatocellular carcinoma (HCC) remains a major global health burden due to its high prevalence and mortality. Emerging evidence reveals that microRNA (miRNA) plays a vital role in cancer pathogenesis and is widely involved in the regulation of signaling pathways via their targeting of downstream genes. MiR-21-3p, a liver-enriched miRNA, and SMAD7, the negative regulator of the TGF-β signaling pathway, likely exert a vital influence on HCC progression. Aims Here, we explore the role of the miR-21-3p-SMAD7/YAP1 axis on HCC pathogenesis. Methods MiRNA microarray analysis was performed for miRNA screening. The dual-luciferase assay was adopted for target verification. Expression of miRNA and related genes were quantified via qRT-PCR, western blotting, and immunohistochemical staining. Flow cytometry and the transwell migration assay were used to detail cell apoptosis, invasion and metastases. Rat models were established to explore the role of the miR-21-3p-SMAD7/YAP1 axis in hepatocarcinogenesis. Bioinformatics analysis was conducted for exploring genes of clinical significance. Results MiR-21-3p levels were found to be significantly elevated in hepatocellular carcinoma and indicate poor overall survival. High miR-21-3p levels were associated with advanced tumor stages (P = 0.029), in particular T staging (P = 0.026). Low SMAD7/high YAP1 levels were confirmed in both HCC and rat models with advanced liver fibrosis and cirrhosis. Besides, SMAD7 was demonstrated to be the direct target of miR-21-3p. The effect of MiR-21-3p on tumor phenotypes and YAP1 upregulation could be partly reversed via the restoration of SMAD7 expression in HCC cell lines. Overexpression of YAP1 after miR-21-3p upregulation promoted expression of nuclear transcription effector connective tissue growth factor. Co-survival analysis indicated that lower miR-21-3p/higher SMAD7 (P = 0.0494) and lower miR-21-3p/lower YAP1 (P = 0.0379) group patients had better overall survival rates. Gene Set Variation Analysis revealed that gene sets related to miR-21-3p and SMAD7 were significantly associated with the TGF-β signaling pathway in HCC. Conclusion MiR-21-3p promotes migration and invasion of HCC cells and upregulation of YAP1 expression via direct inhibition of SMAD7, underscoring a major epigenetic mechanism in the pathogenesis of HCC.